DanTox: a novel joint research project using zebrafish (Danio rerio) to identify specific toxicity and molecular modes of action of sediment-bound pollutants - Keiter, Steffen; Peddinghaus, Sabrina; Feiler, Ute; Kais, Britta; Hafner, Christoph; Ho, Nga Yu; Rastegar, Sepand; Otte, Jens C.; Ottermanns, Richard; Reifferscheid, Georg; Strähle, Uwe; Braunbeck, Thomas; et al. (Journal of soils and sediments, 2010)
The European Water Framework Directive aims to achieve a good ecological and chemical status in surface water of European rivers by the year 2015. Since sediments and particulate matter act as secondary sources for pollutants, applied sediment toxicology is perceived to play a major role for obtaining new knowledge that can contribute to successful attainment of the goal. However, the existing bioassays for sediment toxicity analyses do not provide sufficient data concerning bioavailability of environmental pollutants. In this regard, there is an urgent need to combine sediment contact assays with gene expression analysis to investigate mechanism-specific sediment toxicity.